Analysis of the conditions of phase equilibrium and influence of the united heat and mass transfer on the effectiveness of separation in the inertial-filtering separator - Liaposhchenko, Oleksandr; Nastenko, Olha (Publishing House of Lviv Polytechnic National University, 2015)
In this paper the basic thermodynamic parameters that have the greatest impact on the efficiency of the separation processes of gas-liquid mixtures and phase equilibrium in such systems are considered. The general characteristics of separation processes based on phase equilibrium are given. The main approaches to the calculation of phase equilibrium and coupled heat are analyzed. Possible ways of gas separation technology improvement and development are explored. Розглянуто основні термодинамічні параметри, які мають найбільший вплив на ефективність протікання процесів розділення газорідинних сумішей, а також на фазову рівновагу таких систем. Дана загальна характеристика процесів сепарації з урахуванням фазової рівноваги. Проаналізовано основні підходи до розрахунку фазової рівноваги і сполучного теплообміну. Виявлено можливі шляхи удосконалення та розвитку газосепараційної техніки.
Аналіз умов фазової рівноваги і впливу сполученого тепломасообміну на ефективність процесу розділення в інерційно-фільтруючому сепараторі
Keywords: modeling; equilibrium; gas-liquid mixture; critical parameters; phase equilibrium constant; thermodynamic parameters; condensation; моделювання; рівновага; газорідинна суміш; критичні параметри; константа фазової рівноваги; термодинамічні параметри; конденсація